Meta-analysis of randomized controlled trials for the development of the International Federation for Surgery of Obesity and Metabolic Disorders-European Chapter (IFSO-EC) guidelines on multimodal strategies for the surgical treatment of obesity - De Luca, Maurizio; Belluzzi, Amanda; Angrisani, Luigi; Bandini, Giulia; Becattini, Barbara; Bueter, Marco; Carrano, Francesco Maria; Chiappetta, Sonja; Cohen, Ricardo V.; Copaescu, Catalin; Di Lorenzo, Nicola; Emous, Marloes; et al. (Diabetes, obesity and metabolism, 2025)
Abstract Background Randomized, controlled trials (RCTs) comparing the effectiveness of metabolic bariatric surgery (MBS) in addition to one or more treatment interventions for obesity (i.e., lifestyle structured interventions?LSI, medical therapy?MT, obesity management medication?OMM or endobariatric procedures?EP) are lacking. This study aims to assess the effectiveness of multiple simultaneous (before or immediately after MBS) interventions for treating obesity. Methods We performed a meta-analysis including all RCTs enrolling patients undergoing different MBS procedures add-on to other anti-obesity strategies (LSI, MT, OMM or ES) versus MBS alone, with a duration of at least 6?months. The primary outcome was BMI at the end-point; secondary end-points included percentage total and excess weight loss (%TWL%, and EBWL%), total weight loss (TWL), fasting plasma glucose (FPG), HbA1c, surgical and non-surgical severe adverse events (SAE), mortality, remission of type 2 diabetes, hypertension, dyslipidemia and health-related quality of life (HR-QoL). Results A total of 25 RCTs were retrieved. The addition of either OMM (i.e., liraglutide) or EP (i.e., intragastric balloon?IB, endosleeve-ES) to MBS was associated with a significantly lower BMI at the end-point (p?=?0.040). The addition of liraglutide only to MBS was associated with a greater %EWL%, but not %TWL and TBWL (p?=?0.008). Three trials evaluated end-point HbA1c, showing a significant reduction in favour of liraglutide as an add-on therapy to MBS (p?=?0.007). There was no mortality. Conclusions MBS combined with non-surgical approaches appears more effective than MBS alone in reducing BMI. Further RCTs on combined therapies to MBS for severe obesity are needed to enhance the tailoring of treatment for severe obesity.